Bioecological Properties And Agrotechnology Of The Medicinal Plant Convallaria Majalis L. In The Territory Of Karakalpakstan (Texas Journal of Agriculture and Biological Sciences, 2025)
The article considers the importance of crop rotation in the cultivation of medicinal plants. It is shown that the crop rotation system has a positive effect on the growth and development of plants. Information is provided on the cultivation technology of the marigold plant. The length of the plant is 8-10 cm, width is 0.5-0.7 cm, and the soil substrate (filled with sand and leaf humus in a 1:1 ratio) is transferred to boxes to a depth of 4-6 cm. The distance between the plants is 4 cm, the distance between the rows is 15- 20 cm, and they are planted in moist soil, then watered. The rhizomes planted in autumn are strong, and their vegetative development is faster than in spring. It is advisable to place 20 plants per 1 m of land.